Strategi Marketing Mix 4p dalam Mewujudkan Sekolah Unggulan - Muna Fauziah; Khakimatusodiqoh Khakimatusodiqoh; Muhyidin Muhyidin; Bahrun Ali Murtopo (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2022)
This research is motivated by the phenomenon of increasingly stringent educational institution competition at all levels, especially at the Early Childhood level. In this regard, this study aims to determine the application of the 4P marketing mix strategy in realizing superior schools in RA Queen Al Khadijah District. The method used by researchers in researching this case is to use a qualitative approach, because a qualitative approach is used to describe, describe systematically, factually and accurately about the facts and the nature of the relationship between the phenomena being investigated. The sources of data obtained are by using observation, interviews, and documentation. The strategy used by RA Queen Al Khadijah is to apply a marketing mix strategy or better known as 4P (Product, Price, Place, Promotion). Product, price, place and promotion strategies were all carried out by RA Queen AL Khadijah in providing satisfaction to consumers, increasing the number of students, the quality of students so that the label as a superior school would be given by consumers.